Pengaruh Disiplin Kerja, Komunikasi Dan Kompetensi Kerja Terhadap Kinerja Karyawan PT Citra Shipyard - Mayesti Mayesti; Wasiman Wasiman (Komunitas Dosen Indonesia, 2023)
A companies that is exist competed, of course, has effective managements in order improved the performances of employees in accordance with their fields. It was found there are a decrease in the performance of PT Citra Shipyard employees caused by several aspects such as work discipline, communication and work competence. The aims of this studies are determining the effect of work discipline, communication and work competence on the performance of PT Citra Shipyard employees. This study used sample of 146 respondents. The results of this study are work discipline, communication and work content have a positive and significant effect on employee performance. The implication of this research is that companies can pay attention to aspects of work discipline, communication and work competence to improve and improve employee performance. In addition, if the three variables are applied simultaneously, it will have a major effect on improving the performance of employees of PT Citra Shipyard.